1982
DOI: 10.1002/etc.5620010108
|View full text |Cite
|
Sign up to set email alerts
|

Fate of 2,3,7,8‐tetrachlorodibenzo‐P‐dioxin (TCDD) in an outdoor pond and in model aquatic ecosystems

Abstract: Environmental fate of TCDD was studied in an aquatic ecosystem, using an outdoor pond which had been dosed initially with 53.7 ppt of14C‐TCDD. The levels of radiocarbon reached an equilibrium in pondweeds after one month, in fish after two months and in the sediment after six months. Using the identical components from the outdoor pond, roughly comparable data were obtained in the laboratory for short‐term distribution of radiocarbon. The largest source of variance and discrepancy between the outdoor and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The differences between the two studies may be attributed to the different sizes of the ponds, especially the plant compartment, as well as to different rates of transformation of the T,CDD isomers. A plant/sediment ratio of 0.5 was found by Tsushimoto et al [2], which compares with a ratio o f 0.02 in the present study. An additional factor influencing the apparent dissipation rates in sediment in the present study and in the pond used by Tsushimoto et al [2] was the deposition of plant material to which T,CDD was sorbed, especially at the end of the growing season.…”
Section: Sunlight Photodegradationsupporting
confidence: 81%
See 2 more Smart Citations
“…The differences between the two studies may be attributed to the different sizes of the ponds, especially the plant compartment, as well as to different rates of transformation of the T,CDD isomers. A plant/sediment ratio of 0.5 was found by Tsushimoto et al [2], which compares with a ratio o f 0.02 in the present study. An additional factor influencing the apparent dissipation rates in sediment in the present study and in the pond used by Tsushimoto et al [2] was the deposition of plant material to which T,CDD was sorbed, especially at the end of the growing season.…”
Section: Sunlight Photodegradationsupporting
confidence: 81%
“…For a large outdoor pond, Tsushimoto et al [2] reported that 49.7% of 2,3,7,8-T4CDD added at 53.7 ng/L was still present 1 year after the addition of the chemical, with most of the I4C present in the sediment (12.5%) and in pond weeds (87.5%). The differences between the two studies may be attributed to the different sizes of the ponds, especially the plant compartment, as well as to different rates of transformation of the T,CDD isomers.…”
Section: Sunlight Photodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for calibrating the microcosm with the pond is apparent. Tsushimoto et al (1982) compared the fate of 2,3,7 ,8-tetrachlorodibenzop-dioxin (TCDD) in an outdoor pond (man-made) and in a 16-cm-diameter glass bottle microcosms. Data from each test system were roughly comparable for short-term distribution behavior.…”
Section: Fate Studiesmentioning
confidence: 99%
“…The PCDDs and PCDFs quickly partition to particulate organic carbon and dissolved organic carbon (DOC) in the water column and sediment after entering an aquatic system [6][7][8]. The fate of PCDDs in natural waters and sediments has been more closely experimentally examined than has the fate of PCDFs [9][10][11][12] because of the toxicity of the 2,3,7,8-tetrachlorodibenzo-p-dioxin (2,3,7,8-TCDD) congener. When added to enclosures or ponds, pseudo-first-order half-lives (t ½ ) in the water column range from 0.4 [13] to 4 d [7][8][9] for various PCDD congeners.…”
Section: Introductionmentioning
confidence: 99%